J. G. Montes Cala, M. Sánchez Ortiz de Landaluce y R. J. Gallé Cejudo (eds.), Plutarco, Dioniso y el vino, Madrid, Ediciones Clásicas, 1999, X + 540 pp. (Minerva, 2019)
Review: J. G. Montes Cala, M. Sánchez Ortiz de Landaluce y R. J. Gallé Cejudo (eds.), Plutarco, Dioniso y el vino, Madrid, Ediciones Clásicas, 1999, X + 540 pp.